Is rating of perceived exertion a valuable tool for monitoring exercise intensity during steady-state conditions in elite endurance athletes? - Losnegard, T.; Skarli, S.; Hansen, J.; Roterud, S.; Svendsen, I. S.; Rønnestad, B. R.; Paulsen, G. (International Journal of Sports Physiology and Performance, 2021)
Purpose: Rating of perceived exertion (RPE) is a widely used tool to assess subjective perception of effort during exercise. The authors investigated between-subject variation and effect of exercise mode and sex on Borg RPE (6-20) in relation to heart rate (HR), oxygen uptake (VO2), and capillary blood lactate concentrations.